Jewish choices, Jewish voices. Sex and intimacy - Dorff, Elliot N.; Newman, Louis E., 1956- (Philadelphia, PA : Jewish Publication Society, 2010)
In the newest addition to the Jewish Choices, Jewish Voices series, co-editors Elliot Dorff and Danya Ruttenberg have brought together a diverse group of Jews to comment on how Judaism affects their views and actions regarding sex. Contributors range from adult movie actor Ron Jeremy, to renowned feminist scholar Martha Ackelsberg, to noted writer and blogger Esther Kustanowitz, as well as rabbis, doctors, social workers, and activists. They discuss issues of monogamy, honesty, and communication in dating and marriage; testing for and disclosure of STDs; abortion, sex education, sex work, and sexuality.
Case 1: Dating Ethics -- Case 2: Sexual Consequences -- Case 3: Sex Work and Pornography -- Case 4: Sexual Negotiation -- Conclusion: The Ethics of Sex.
Includes bibliographical references (pages 145-146) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Jewish ethics; Jews -- Identity; Sex -- Religious aspects -- Judaism; Morale juive; Juifs -- Identité.; Sexualité -- Aspect religieux -- Judaïsme.; RELIGION -- Judaism -- Theology; Jewish ethics; Jews -- Identity; Sex -- Religious aspects -- Judaism